2022
DOI: 10.3390/v14030477
|View full text |Cite
|
Sign up to set email alerts
|

Immunoregulatory Intestinal Microbiota and COVID-19 in Patients with Type Two Diabetes: A Double-Edged Sword

Abstract: Coronavirus disease 2019, or COVID-19, is a major challenge facing scientists worldwide. Alongside the lungs, the system of organs comprising the GI tract is commonly targeted by COVID-19. The dysbiotic modulations in the intestine influence the disease severity, potentially due to the ability of the intestinal microbiota to modulate T lymphocyte functions, i.e., to suppress or activate T cell subpopulations. The interplay between the lungs and intestinal microbiota is named the gut–lung axis. One of the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 175 publications
(195 reference statements)
1
25
0
Order By: Relevance
“…Leptospires are capable of altering gut microbiota. Similar mechanisms, according to which infectious agents change the gut microbiota, have also been revealed for SARS-CoV-2, Influenza, M. tuberculosis, and some other microorganisms (111)(112)(113)(114). Most of the current studies emphasize the possible influence of these microbiota changes on the course of diseases (115)(116)(117).…”
Section: Discussionsupporting
confidence: 59%
“…Leptospires are capable of altering gut microbiota. Similar mechanisms, according to which infectious agents change the gut microbiota, have also been revealed for SARS-CoV-2, Influenza, M. tuberculosis, and some other microorganisms (111)(112)(113)(114). Most of the current studies emphasize the possible influence of these microbiota changes on the course of diseases (115)(116)(117).…”
Section: Discussionsupporting
confidence: 59%
“…Comorbidity is also needed to be considered when conducting telerehabilitation studies for COVID-19. Studies found that hypertension and type 2 diabetes are the most common comorbidities, which may induce a more severe course of COVID-19 ( 56 , 60 , 61 ). Of the included studies, only three studies ( 22 , 23 , 32 ) measuring different outcomes reported comorbidities, which prevents further analysis of comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly used diabetes medications are metformin and insulin. Theoretical evidence suggests that metformin may be beneficial for reducing proinflammatory and profibrotic states ( 2 , 10 , 11 ) and improving immune response ( 12 ). Insulin treatment may increase the risk of poor prognosis by increasing renal Angiotensin Converting Enzyme 2 (ACE2) expression in diabetic mice ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID‐19), caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS‐CoV‐2), was first reported in December 2019 ( 1 , 2 ). The severity of COVID-19 ranges from asymptomatic to severe infection leading to death ( 1 ).…”
Section: Introductionmentioning
confidence: 99%